Colombia Case Study : The Subsidized Regime of Colombia’s National Health Insurance System - Montenegro Torres, Fernando; Bernal Acevedo, Oscar (World Bank, Washington, DC, 2013)
This case study provides an overview of the contribution of Colombia's compulsory health insurance, particularly its Subsidized Regime (SR), to universal health care coverage in the country, and the current challenges the SR faces. The case study is based on discussions with stakeholders from academia and the public and private sectors. The report is divided into four sections: (1) country context and health outcomes; (2) the SR within the institutional architecture of the national health insurance system; (3) the subsidized regime: considerations on equity in the context of the public debate on the right to health care in Colombia; and (4) policy decisions and key areas of the agenda for the short and medium term.